KEAMANAN DATA PEMBELAJARAN ONLINE JARINGAN KOMPUTER DI PERGURUAN TINGGI - Sallu, Sulfikar -; Qammaddin, Qammaddin (Instruksional, 2020)
Data security is a process in maintaining and securing information packages in exchanging data in the digital world. The purpose of this study is to produce a method for securing online data transactions. The method used is a literature review by comparing several data security methods that already exist in online learning. The results achieved are a method or method that can be used in online learning for computer network courses. The implication is that the Computer Network course given online will have an online data security system in the teaching and learning process.